DOI: 10.11606/t.18.2002.tde-29052006-171714
|View full text |Cite
|
Sign up to set email alerts
|

Contribuição ao estudo da instabilidade lateral de vigas pré-moldadas

Abstract: Debs, por aceitar o desafio de um trabalho de doutorado, pela amizade, pelo apoio e pelos ensinamentos.Ao Prof. Irineu da Silva do Departamento de Transportes, pelo grande apoio técnico na realização de nosso programa experimental. À Wild Comercial Ltda, pelo empréstimo das Estações Totais. Com muita gratidão, ao doutorando Artur Pantoja Marques e ao técnico Paulo Sérgio Batista (Paulinho), pela eficiência das leituras dos deslocamentos com as Estações Totais, pela gentileza e por cederem seu tempo em favor de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
14

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 18 publications
0
10
0
14
Order By: Relevance
“…In these situations, the provisory supports do not restraint the element against twist rotation and lateral deflection, as occurs in permanent phase. In general, transitory situations are considered critical for lateral buckling of precast beams, as presented by Lima [1] and [2], El Debs [3] and Krahl [4]. Typically, beams have low lateral flexural stiffness and when undergo rotation about its longitudinal axis part of the self-weight acts laterally.…”
Section: Introductionmentioning
confidence: 99%
“…In these situations, the provisory supports do not restraint the element against twist rotation and lateral deflection, as occurs in permanent phase. In general, transitory situations are considered critical for lateral buckling of precast beams, as presented by Lima [1] and [2], El Debs [3] and Krahl [4]. Typically, beams have low lateral flexural stiffness and when undergo rotation about its longitudinal axis part of the self-weight acts laterally.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the initial rotation was recorded for all beams that can be the effect of eccentricity of the lifting cables and initial lateral displacements which induces rotation. (MAST, 1994) and (LIMA, 2002) presented results of tests to failure of precast prestressed and nonprestressed concrete beams, respectively, under controlled rotation imposed at both ends. These studies show the rotation capacity of concrete beams subjected only to self-weight.…”
Section: Reported Experimental Studiesmentioning
confidence: 99%
“…For the beam tested by (MAST, 1994), cracking was detected approximately at a rotation of 10 degrees, which corresponded to a lateral displacement of 127 mm and at failure a rotation of 32 degrees with 762 mm of lateral displacement at midspan. The cracking rotation for the beam tested by (LIMA, 2002) was 15 degrees and at failure 54 degrees. Both studies showed that the elements suffer small torsional strains along the span when subjected only to self-weight and to a controlled rotation imposed at both ends.…”
Section: Reported Experimental Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Diversas causas podem influenciar para que a instabilidade ocorra. Dentre elas estão a esbeltez da peça (REVATHI; MENON, 2007;GIRIJA;MENON, 2011), imperfeições geométricas (HILL; DICK; TADROS, 2009), condições de transporte (MAST, 1993), de içamento (LIMA, 2002;KRAHL, 2014) e de apoio temporário da viga (KRAHL, 2014;HAMILTON, 2012;HURFF;KAHN, 2012a;HARPER;CONSOLAZIO, 2013).…”
Section: Capítulo 1 Introdução 11 Considerações Iniciaisunclassified